(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Over the past few years, chatbot research has accelerated. The performance, acceptance, and deployment of these tools for internal team communication or customer communication are the subject of research by academics and practitioners. Although there are a ton of current studies available, not all of them discuss the implications of Chatbots for the digital business transformation. The primary goal of the research discussed in this paper was to conduct a systematic review of Chatbots, identify their function in the transformation of digital businesses, and identify the areas that need more research, benefits and the gap areas for innovation of the Chatbots for E business using the technology.